Jerome's commentaries on the Pauline epistles and the architecture of exegetical authority - Cain, Andrew (Oxford early Christian studies, 2021)
In the late fourth and early fifth centuries, during a fifty-year stretch sometimes dubbed a Pauline 'renaissance' of the western church, six different authors produced over four dozen commentaries in Latin on Paul's epistles. Among them was Jerome, who commented on four epistles (Galatians, Ephesians, Titus, Philemon) in 386 after recently having relocated to Bethlehem from Rome. His commentaries occupy a time-honored place in the centuries-long tradition of Latin-language commenting on Paul's writings. Adopting a cross-disciplinary approach, Cain comprehensively analyzes the commentaries' most salient aspects - from the inner workings of Jerome's philological method and engagement with his Greek exegetical sources, to his recruitment of Paul as an anachronistic surrogate for his own theological and ascetic special interests.